Testing of JTD Engine Fueled with Hemp and Rapeseed Oil Esters - Adam Koniuszy; Małgorzata Hawrot-Paw; Wojciech Golimowski; Tomasz Osipowicz; Konrad Prajwowski; Filip Szwajca; Damian Marcinkowski; Wojciech Andrew Berger (Energies, 2025)
Alternative fuels to fossil fuels have been a focus of research since the 1980s, due to the oil crisis. Biofuels for diesel engines are obtained from various types of fats, primarily vegetable oils. Soybean and rapeseed oil are mainly used to produce biofuels. The aim of the research undertaken was to compare the performance characteristics of a 1.3 JTD engine fueled with methyl esters from hemp compared to biofuels made from rapeseed and fossil fuels. Energy parameters and exhaust emissions were measured. The fuels used were 100% biofuels obtained from vegetable oils by transesterification using methanol and KOH. It was shown to be possible to use HME (hemp methyl esters) biofuels as an alternative fuel to RME (rapeseed methyl esters) or DF (diesel fuel) without significant changes in engine performance. The density and heat of combustion of such fuels results in a 6% reduction in power and 17% in NOx emissions, as well as a decrease in HC (hydrocarbons), CO2, and smoke emissions.